Narrowing the Gap between Anion and Strong Ion: A Current Perspective - Kenrick Berend; Andrew L. Lundquist (Medical Research and Its Applications Vol. 10, 2024)
Background: A true “ion gap” does not exist in vivo which makes the anion gap a fundamental tool to evaluate acid-base disorders. The strong anion gap (SIG), which is the foundation of the Stewart acid-base method, is a term that many doctors are unaware of, despite its significance in understanding acid-base pathophysiology. It is unknown how much the anion gap and the strong ion gap differ quantitatively. Aim: The present study aimed to discuss narrowing the gap between the anion gap and the strong ion gap. Methods: The quantitative difference between the SIG and the albumin-corrected anion gap (AGc) was calculated at a wide range of albumin, phosphorus and pH levels. Results: At an albumin level of 1-3 g/dl and pH from 6.9-7.3, the contribution difference of albumin between the AGc and the SIG was maximally -0.97 to 0.51 mEq/L. In metabolic alkalosis and hypoalbuminaemia, the AGc differed less than 2 mEq/L from the SIG. The calculated contribution of phosphorus was higher in the SIG with phosphorus levels > 2 mmol/L and could be accounted for in the anion gap with the conversion factor 1.76x[phosphorus, in mmol/L]. Conclusion: The SIG and the AGc were nearly identical across a wide range of values, particularly when albumin and phosphorus levels were low. The anion gap would be more precise incorporating the major components of the SIG using the equation: [Na+] - [Cl-] - [HCO3-] - 2.5x[albumin, in g/dL] – 1.76x[phosphorus, in mmol/L], with an arbitrarily set reference range of 1 + 5 mEq/L. To have a better understanding of the pathophysiology and to be more accurate, the anion gap, or perhaps a more logical term, “the ion gap” should be written to become almost identical to the SIG.